Modalities and costs of familiar and social support to chronically ill patients: a pilot investigation in the Udine health district - Petrinco, Michele (Metodološki zvezki, 2006)
The main objective of this study was to quantify the characteristics of social networks in a sample of elderly ill patients. These patients who had chronic illness were receiving home based care, in an Italian district during 2001. Both patients and caregivers were interviewed. The analysis of the care givers questionnaire was conducted to avoid missing answers when gathered from the patients. This method also enabled a better understanding of the impact of social support on chronic illness pathologies. Further more, it allowed the investigation of the patientsć network, the caregiversć point of view, the costs, the quality of care and the assessment of sociodemographical data of both. Results highlighted the particular situation of patients, characterized by high dependence from other persons especially for every day activities. Most of the caregivers were family members for the number of persons involved and for the time spent for the care. The network support maintenance and mobilization costs evaluation was faced suggesting three different strategies, according to three different ways of time-opportunity calculation, of the informal caregivers.
Keywords: Social relief; Socialna podpora; Social networks; Družbena omrežja; Družina; Family; Patients; Bolniki; stroški; družboslovno raziskovanje